Linux : learning the essentials - James, K.L. (New Delhi : Phi Learning pvt Ltd, 2012)
The book aims at providing a through understanding of the essentials and the workings of Linux Operating System (OS). It explores the technicalities of this free and open source OS so as to enable readers to harness the full power of Linux. The book discusses its silent features, different stages of its development, its basic operations and installation steps, and then describes the desktop environments, file management, administration, and basic Linux commands.